COMPLICATIONS OF PULMONARY TUBERCULOSIS - Fatilloeva Gulshoda Zokirovna (Web of Journals Publishing, 2025)
Pulmonary tuberculosis remains a significant public health problem worldwide, despite advances in diagnostics and treatment. This article reviews the main complications resulting from tuberculosis, such as pleurisy, pulmonary hemorrhage, and the development of bronchiectasis. In particular, the importance of timely detection and a comprehensive approach to the treatment of these complications, which can significantly worsen the quality of life of patients and lead to death, is emphasized (Kuznetsov, 2021; Petrova et al., 2022). Risk factors and recommendations for the prevention of complications in high-risk groups are also discussed. Understanding the relationship between tuberculosis and its complications is key to improving the effectiveness of medical care and improving prognosis for patients.
Keywords: Pulmonary tuberculosis, complications, pleurisy, bronchiectasis , diagnostics.